تأثير رأس المال البشري على أداء الابتكار في الجامعات السّورية (دراسة ميدانية في جامعة تشرين) - ديب, كندة; مرهج, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت هذه الدّراسة إلى التعرّف على العلاقة بين رأس المال البشري وأداء الابتكار في جامعة تشرين، من خلال تحديد تأثير المهارة، والمعرفة، والخبرة، وقد اعتمد الباحث على المقاربة الاستنباطية كمنهج عام للبحث، واتباع منهجية المسح، ام بتوزيع الاستبيان على 360 فرد من أعضاء الهيئة التعليمية في جامعة تشرين، ومن ثمّ أجريت دراسة ميدانيّة بغرض بيان هذه العلاقة. وقد خلصت الدّراسة إلى وجود علاقة طردية معنوية بين رأس المال البشري وأداء الابتكار. ثمّ قدّم ملخّص لأهمّ النتائج التي تمّ التوصّل إليها، حيث كانت النتيجة الرئيسة الأهمّ هي امتلاك جامعة تشرين لرأس مال بشري قادر على أداء الابتكار (الجذري، والتدريجي)، ثم تمّ عرض بعض المقترحات والتوصيات لتحسين العلاقة، والتي أهمها: ضرورة العمل على تنمية المهارات والمعارف المتوافرة واكتساب المزيد منها بهدف تعزيز أداء الابتكار لأعضاء الهيئة التعليمية في جامعة تشرين.This study aimed at identifying the relationship between the human capital and innovation performance in Tishreen University. By Identifying the Impact of each the skill, knowledge, and experience. The researcher relied on the Deductive Approach as a general method. He follows a survey methodology, and he gave a questionnaire to 360 people, they are members of the Teaching Staff in Tishreen University, He also made a field Study to show this relationship, The main result of the study was that there a positive significant relationship between the human capital and innovation performance. We have provided a summary of the main result that have found out is that the possession of Tishreen University of human capital capable to innovation performance (radical and Incremental). With the presentation of some of the proposals and recommendations to improve the relationship including the need to work on the development of skills and knowledge and gain more of it, in order to enhance innovation performance to the members of the Teaching Staff in Tishreen University.